Short-chain fatty acids contribute to neuropathic pain via regulating microglia activation and polarization. (February 2021) - Zhou, Feng; Wang, Xian; Han, Baoyu; Tang, Xiaohui; Liu, Ru; Ji, Qing; Zhou, Zhiqiang; Zhang, Lidong
Microglia activation and subsequent pro-inflammatory responses play a key role in the development of neuropathic pain. The process of microglia polarization towards pro-inflammatory phenotype often occurs during neuroinflammation. Recent studies have demonstrated an active role for the gut microbiota in promoting microglial full maturation and inflammatory capabilities via the production of Short-Chain Fatty Acids (SCFAs). However, it remains unclear whether SCFAs is involved in pro-inflammatory/anti-inflammatory phenotypes microglia polarization in the neuropathic pain. In the present study, chronic constriction injury (CCI) was used to induce neuropathic pain in mice, the mechanical withdrawal threshold, thermal hyperalgesia were accomplished. The levels of microglia markers including ionized calcium-binding adaptor molecule 1 (Iba1), cluster of differentiation 11b (CD11b), pro-inflammatory phenotype markers including CD68, interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and anti-inflammatory phenotype markers including CD206, IL-4 in the hippocampus and spinal cord were determined on day 21 after CCI. The results showed that CCI produced mechanical allodynia and thermal hyperalgesia, and also increased the expressions of microglia markers (Iba1, CD11b) and pro-inflammatory phenotype markers (CD68, IL-1β, and TNF-α), but not anti-inflammatory phenotype marker (CD206, IL-4) in the hippocampus and spinal cord, accompanied by increased SCFAs in the gut. Notably, antibiotic administration reversed these abnormalities, and its effects was also bloked by SCFAs administration. In conclusion, data from our study suggest that CCI can lead to mechanical and thermal hyperalgesia, while SCFAs play a key role in the pathogenesis of neuropathic pain by regulating microglial activation and subsequent pro-inflammatory phenotype polarization. Antibiotic administration may be a new treatment for neuropathic pain by reducing the production of SCFAs and further inhibiting the process of microglia polarization.